Evaluation of the Reliability of Hospital Supplementary Building Structures Under Service Loads - Mahfuda, Anno; Winarsih, Anita Lestari Condro (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2025)
The capacity of a building to bear the service loads that will be placed on it is a structural requirement. Reinforced concrete is the primary material utilized in this study. Its primary function is to endure the service load and fulfill the requirements stated in the relevant Indonesian standards. SAP2000, employing the finite element method, is utilized in this study to evaluate the building structure's performance in accordance with the relevant service loads. Based on the analysis, the structural element result remains below the allowable standard in terms of deflection; therefore, it does not require an adjustment in the size or quality of the service load performance. The study also reveals that the structural elements of the concrete slab are reacting to the stress and deflection that occur due to the structural service load. Based on the analysis, the highest stress in the deflection of the beam is 0.5816 mm, the highest deflection of the column is 0.089 mm, and the highest tensile stress of the concrete slab is 0.932 MPa. This study's result is an essential concern, where other structural elements, including columns, sloops, and beams, are safe enough to operate according to appropriate standards.